1977
DOI: 10.1111/j.1365-2265.1977.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Theoretical Description of the Binding of Thyroid Hormones by Serum Proteins

Abstract: A theoretical model is proposed which describes the binding of thyroid hormones to serum proteins in terms of easily determined parameters, Not only free hormone concentration but also the distribution of hormone among various binding sites may be computed. The mathematical approach is capable of dealing with models of differing complexity of binding from simple 'one binding site per protein molecule' systems to those involving 'negative co-operativity'. The approach gives predictions of thyroid function param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

1979
1979
1997
1997

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…The mean concentration of normal u-TBG obtained thus was 15.4 mg/l or 257 nmol/l, assuming a TBG molecular weight of 60 000 daltons (Marshall & Pensky, 1971). This is more than twice the value of 95.8 nmolil calculated by Prince & Ramsden (1977). One of the reasons for this discrepancy may be the difference in the TBG concentration; the TBG level in their measurements is half of that in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…The mean concentration of normal u-TBG obtained thus was 15.4 mg/l or 257 nmol/l, assuming a TBG molecular weight of 60 000 daltons (Marshall & Pensky, 1971). This is more than twice the value of 95.8 nmolil calculated by Prince & Ramsden (1977). One of the reasons for this discrepancy may be the difference in the TBG concentration; the TBG level in their measurements is half of that in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…TBG possesses binding sites of much higher affinity for T, and T3 than those of TBPA and Alb (22), and the increased serum TBG level determines the serum thyroid hormone concentrations in newborns (14). In attempting to evaluate the saturation of TBG binding sites, the individual ratios between serum concentrations of thyroid hormones and TBG were calculated.…”
Section: Nsmentioning
confidence: 99%
“…More recently, Bannai et al (1985) have shown slight suppression of TBG levels in severely thyrotoxic patients, although mildly thyrotoxic individuals did not differ significantly from their normal controls. In this study, since serum TBG levels were actually at the upper end of the normal range, the most likely explanation for a discrepancy between total and free T4 levels is diminished affinity of TBG (Prince & Ramsden, 1977;Yoshida et al, 1981) and TBPA (Ingbar et al, 1965;Oppenheimer et al, 1963) for T4.…”
Section: Discussionmentioning
confidence: 55%